Integrated modeling and operation optimization of circulating cooling water system based on superstructure. (25th December 2017) - Zhu, Xiaochen; Wang, Fuli; Niu, Dapeng; Zhao, Luping
Highlights: Functional section division method, multi-model and superstructure are proposed. Integrated model of industrial circulating cooling water system is established. Simulation experiment based on integrated model is carried out. Running cost can be reduced by operation optimization based on integrated model. Abstract: An integrated modeling method based on system mechanism analysis and superstructure is presented in this work to completely describe the performance of an industrial circulating cooling water system. A functional section division method is proposed based on the analysis of the operation principle of the circulating cooling water system. Then, multiple models are established for running equipment considering the diversity of actual pipe network equipment. The superstructure method is used to design the model structure framework. An integrated model, which has a good application range and can describe the complete structure information and operating status of the system, is established based on the above modeling method. In addition, the performance of the integrated model is verified by the simulation experiment with actual network data. Finally, the operation optimization of the circulating cooling water system is carried out. The simulation results show that the proposed method can effectively reduce the running cost of the system.